2011
DOI: 10.5021/ad.2011.23.2.201
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Myopericytoma on the Lower Leg

Abstract: Fig. 1. A soft tissue masscovered with overlying normal skin on the posterior side of the right lower leg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A limitation of this approach is that cases of myopericytomas that have been reported under different terminologies in the past are not included in our review. The typical clinical and histopathologic findings of the reported cutaneous myopericytomas is listed in table 1 [ 2 , 4 , 5 , 6 , 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Most patients were male (male:female = 1.5:1), and patient age ranged from 13 to 87 years (median = 47 years).…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this approach is that cases of myopericytomas that have been reported under different terminologies in the past are not included in our review. The typical clinical and histopathologic findings of the reported cutaneous myopericytomas is listed in table 1 [ 2 , 4 , 5 , 6 , 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Most patients were male (male:female = 1.5:1), and patient age ranged from 13 to 87 years (median = 47 years).…”
Section: Discussionmentioning
confidence: 99%
“…MPCs comprise a mixture of solid cellular areas comprised of oval and spindle shaped cells and vascular channels with prominent branches providing the tumour with both a myofibroma and haemangiopericytoma-like appearances retrospectively [ 6 ]. Depending on the amount of solid to vascular area, can provide great range in histological appearance of MPCs from myofibromatosis to angioleiomyoma and glomus tumours [ 5 , 7 ]. Glomus tumours do demonstrate perivascular arrangement of cells however are not concentrically arranged [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…MPC tumours are rarely infiltrative and recurrence is rare [ 6 ]. It has been suggested that the malignant potential of MPC is strongly associated with the depth of the tumour however only a limited number of cases have been reported and more need to be reviewed with a more prolonged follow up to substantiate this hypothesis [ 4 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pericyte, first described by Zimmermann in 1923, is a pluripotent cell that may differentiate into smooth muscle cells, adipocytes and osteoblasts 8 . In coining the term ‘myopericyte’ in 1992, Dictor et al referred to it as a cell transitional between pericytes and smooth muscle cells of vessels 9 . Neoplasms that display putative pericytic differentiation were first documented as haemangiopericytomas by Stout and Murray in 1942; however, 8 the lack of reliable and reproducible diagnostic features for haemangiopericytoma has resulted in an ill-defined entity that is now largely regarded as a growth pattern rather than a distinct tumour 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Neoplasms that display putative pericytic differentiation were first documented as haemangiopericytomas by Stout and Murray in 1942; however, 8 the lack of reliable and reproducible diagnostic features for haemangiopericytoma has resulted in an ill-defined entity that is now largely regarded as a growth pattern rather than a distinct tumour 10 . It is only in the last 13 years that myopericytoma has been increasingly recognised and defined as a distinct entity 1 – 9 , 11 16 . Myopericytoma is categorised as a tumour that originates from the perivascular myoid cell, and it shares features of smooth muscle and glomus cells 11 .…”
Section: Discussionmentioning
confidence: 99%